Moving toward Universal Coverage of Social Health Insurance in Vietnam : Assessment and Options - Somanathan, Aparnaa; Tandon, Ajay; Dao, Huong Lan; Hurt, Kari L.; Fuenzalida-Puelma, Hernan L. (Washington, DC: World Bank, 2014)
To address the growth in resultant out-of-pocket (OOP) payments and associated problems of financial barriers to access, the government issued several policies aimed at expanding coverage throughout the 1990s and 2000s, particularly for the poor and other vulnerable groups. Universal coverage (UC) can be an elusive concept and is about three objectives: (a) equity (linking care to need, and not to ability to pay); (b) financial protection (ensuring that health care use does not lead to impoverishment); (c) effective access to a comprehensive set of quality services (ensuring that providers make the right diagnosis and prescribe a treatment that is appropriate and affordable; and (d) to ensure that the financing needed to achieve UC is mobilized in a fiscally sustainable manner, and is used efficiently and equitably. The objective of this report is to assess the implementation of Vietnam social health insurance (SHI) and provide options for moving toward UC, with a view to contributing to the law revision process. It analyzes progress to date on the two major goals of the master plan. The report assesses Vietnam's readiness to meet these goals, the challenges it will face in achieving UC, and key reforms needed to overcome those challenges. It does so through a health financing lens, focusing on how resources are mobilized, pooled, and allocated, and how services are purchased. The report also examines the stewardship of financing that is, the organization, management, and governance of SHI as it has direct implications for achieving UC. The report ends by pulling together the recommendations in the form of an implementation road map.